Comparação entre dois tipos de suspensão passiva de barra em condições simuladas de pista de prova normalizada - Pontelli, Cristiano O.; Mucheroni, Mário F.; Balthazar, José M. [UNESP]; Pontes Júnior, Bento R. [UNESP] (FapUNIFESP (SciELO), 2010)
In this paper we conducted several analysis of the simulated dynamic behavior of two passive suspension types of the trailed sprayer booms. The suspension analysis was conducted under conditions of a bump track test ISO 5008, with two levels of speed (5 km h-1 and 15 km h-1) and two track profiles proposed in these standards (bumpy and smooth). It was used the simulations software MATLAB®, SIMULINK® and Visual Nastran ®. The results obtained showed that suspensions of trapezoidal type have good performance at low frequencies input (ω < 0,2 Hz) while suspensions of simple pendulum type have good performance in others conditions.
Comparison between two types of passive boom suspension under simulated conditions of track test
Keywords: Passive boom suspension; Simple pendulum suspension; Twin-link suspension